MAIAC-based climatology of atmospheric iron-oxide dust species from DSCOVR EPIC observations - Go, Sujung; Lyapustin, Alexei; Choi, Myungje; Korkin, Sergey; Wang, Yujie; Hyer, Edward J. (Frontiers in Remote Sensing, 2025)
This study investigates the vertical distribution and seasonal climatology of absorbing iron-oxide minerals, specifically hematite and goethite, in atmospheric dust using the updated MAIAC EPIC version 3 algorithm. Leveraging data from July 2015 to December 2023, the key innovation is the improved Level 2 product which now incorporates Aerosol Layer Height (ALH), enabling the first-ever long-term characterization of their vertical and seasonal distribution globally. Our analysis reveals distinct seasonal and spatial patterns across major dust-emitting regions. Critically, we find that the spectral absorption properties, such as the imaginary refractive index (k) and Single Scattering Albedo (SSA), are strongly proportional to the mass fraction of iron oxides, highlighting the potential of SSA at UV wavelengths as a valuable tool for global monitoring. Furthermore, we confirm that hematite exhibits significant seasonal vertical variability; its concentration is high near the surface in winter but extends up to 2–4 km into the free troposphere in summer, a finding consistent with independent CALIOP observations. The resulting comprehensive climatology provides novel observational constraints for Earth System Models (ESMs), particularly for accurately modeling dust-radiative forcing. The developed methodology is readily applicable to other UV-NIR satellite platforms, such as PACE, GEMS, and TEMPO, demonstrating its broad utility for future atmospheric composition monitoring efforts.